Influence of Insoluble Dietary Fibre on Expression of Pro-Inflammatory Marker Genes in Caecum, Ileal Morphology, Performance, and Foot Pad Dermatitis in Broiler - Mariella Liebl; Martin Gierus; Christine Potthast; Karl Schedle (Animals, 2022)
In a low-fibre diet destined for broilers, the effects of two lignocellulose products and soybean hulls were evaluated regarding their effect on ileal morphometric parameters, caecal gene expression, foot pad dermatitis, and performance. A total of 5040-day-old broilers (Ross 308) were allotted to four treatments and fattened for 36 days applying a three-phase feeding program. The control diet consisted of corn, wheat, and soybean meal. Experimental diets were supplemented with 0.8% lignocellulose product 1, 0.8% lignocellulose product 2, or 1.6% soybean hulls. Tissue samples for caecal expression of inflammation-related genes and ileal morphometries were collected on day 21. Gizzard pH and weights were recorded, and foot pad scores were evaluated at day of slaughter (day 36). In starter (day 1–10) and finisher phase (day 28–36), no effect on the performance was observed. In grower phase (day 11–27), fibre-supplemented diets showed significantly heavier body weights and daily weight gains (p < 0.05). Daily feed intake, feed conversion ratio, and gene expression analysis were unaffected by dietary fibre supplementation. Positive effects regarding ileal morphometrics (higher villi) and foot pad health occurred in fibre-supplemented diets. In conclusion, fibre supplementation improved performance in grower phase and showed beneficial effects regarding ileal morphology and foot pad dermatitis.